Urgensi Pengaturan Pidana Pencemaran Nama Baik dalam Perspektif Hak Asasi Manusia - Emi Puasa Handayani; Zainal Arifin; Rinni Puspitasari; Noval Ghani Baihaki; Diana Kharisma (Fakultas Hukum Universitas Islam Indonesia, 2024)
This paper examines the urgency and potential of criminal regulation concerning defamation, focusing on the perspective of Human Rights (HAM). Defamation presents significant challenges to individual integrity, necessitating a legal approach that aligns with human rights principles. This study delves into the impact of criminal defamation regulation on personal freedom and explores regulatory methods that uphold high human rights standards. Through a thorough analysis of the need to protect one's reputation within the human rights framework, the paper highlights the essential role of human rights norms in shaping fair and balanced legal policies. Furthermore, it discusses the prospects of criminal defamation regulation, considering technological advancements and ongoing social changes, to ensure the protection of individual human rights remains relevant and effective in the modern era.